2020
DOI: 10.7759/cureus.11563
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic Lymphohistiocytosis as the Presenting Manifestation of Relapsed Classic Hodgkin’s Lymphoma in the Presence of Concurrent Human Immunodeficiency Virus, Genital Herpes, Epstein-Barr Virus and Mycobacterium Avium Complex Infection

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening disorder of uncontrolled immune activation which is usually divided into two main types. Primary, which is associated with genetic mutation and familial predisposition and secondary, which is usually associated with infections, malignancies and autoimmune conditions. More often multiple risk factors are present at the time of initial presentation. We report a case where HLH was the presenting manifestation of relapsed Classic Hodgkin's Lymphoma in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…We conducted a review of the PubMed and EMBASE databases of previously reported cases of haemophagocytic syndrome associated with non-tuberculous mycobacterial infection. We found only 12 specific cases of infection by M. avium complex10–21 (Table S1 in the online supplemental appendix 1) and nine cases of infection by other non-tuberculous mycobacteria, including Mycobacterium Kansasii in three cases, Mycobacterium leprae in two cases, and Mycobacterium xenopi , Mycobacterium abscessus , Mycobacterium lentiflavum and Mycobacterium iranicum in one case each22–30 (Table S2 in the online supplemental appendix 1). As in the case of our patient, most of the reported cases correspond to disseminated infections where the lack of localised symptoms delayed the correct diagnosis, and the detection of granulomas in bone marrow biopsy served as an early indicator of infection by non-tuberculous mycobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a review of the PubMed and EMBASE databases of previously reported cases of haemophagocytic syndrome associated with non-tuberculous mycobacterial infection. We found only 12 specific cases of infection by M. avium complex10–21 (Table S1 in the online supplemental appendix 1) and nine cases of infection by other non-tuberculous mycobacteria, including Mycobacterium Kansasii in three cases, Mycobacterium leprae in two cases, and Mycobacterium xenopi , Mycobacterium abscessus , Mycobacterium lentiflavum and Mycobacterium iranicum in one case each22–30 (Table S2 in the online supplemental appendix 1). As in the case of our patient, most of the reported cases correspond to disseminated infections where the lack of localised symptoms delayed the correct diagnosis, and the detection of granulomas in bone marrow biopsy served as an early indicator of infection by non-tuberculous mycobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant tumor cells use 5-10 times more glucose than cells in normal tissue and convert most of the glucose into lactic acid. Increased LDH ensures an extensive glycolysis metabolism, thus storing energy for tumor growth [ 26 ]. Serum ALP mainly comes from the liver and bone, while the BMI of ML patients will lead to the release of ALP in the bone, which will lead to the elevation of serum ALP level.…”
Section: Discussionmentioning
confidence: 99%
“…Infections are the most frequent underlying cause, accounting for a half of all HLH cases, with nearly 70% being secondary to viruses, mainly Herpes virus [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In a review of nearly 2200 cases of adult HLH and several case reports, infections are associated with a worse outcome in the presence of underlying immunodeficiency or cancer, and requirement of intensive care unit admission [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Consistently, hematological and solid cancers are the second most frequent cause of secondary HLH [ 12 , 16 , 19 , 20 , 24 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In a review of nearly 2200 cases of adult HLH and several case reports, infections are associated with a worse outcome in the presence of underlying immunodeficiency or cancer, and requirement of intensive care unit admission [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Consistently, hematological and solid cancers are the second most frequent cause of secondary HLH [ 12 , 16 , 19 , 20 , 24 ]. The main association is lymphoma, particularly T-cell and aggressive NHL, which also carry the highest mortality [ 2 , 12 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation